LEGAL CERTAINTY IN THE EASE OF EFFORT IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 RELATED TO NOTARY PROFESSION - Fadhil Yazid (NOMOI Law Review, 2020)
The start of the 4.0 Industrial Revolution brought many changes to the world. This is the era in which the practice of automation and data exchange, as well as the use of Internet technology, cloud computing, and cognitive computing will colorize various sectors of human life, including the realm of profession. All changes, definitely brings two things: challenges and opportunities. Very wise if we can understand the changes that occurred through the Industrial Revolution of 4.0 and what is the impact for professions, practitioners and officials in the field of law. For a notary, it is time to look at the impact of the 4.0 Industrial Revolution as a challenge and opportunity for future sustainability of the profession. As known, the legal system is divided into two main systems namely common law and civil law, and a small part of the system of religious and mixed law. On both the legal system, the position and authority of the notary is different. A civil law or Latin notary Notary is an official with the authority given by the State to create and issue an authentic deed as well as to provide clarification or legal counseling to the parties concerned. Whereas, the common Law Notary Authority is accepting, noting statements, knowing signatures, certifying copies, all of which are used to support the administrative of other legal proceedings, and not an authentic deed by itself.Keywords: Legal Certainty, Industrial 4.0, Notary